a). (x^4+4x^3+5+8)÷(2x+5)
b). (5x^3+14x^2+12x+8)÷(x+2)
c). (4x^2-4x+1)÷(2x-1)
d). (2x^3+5x^2+6x+15)÷(2x+5)
19 Tìm x, biết
a) (x+2)(x+3)-(x-2)(x+5)=0 ; b) (2x+3)(x-4)+(x-5)(x-2)=(3x-5)(x-4)
c) (8-4x)(x+2)+4(x-2)(x+1)=0 ; d) (2x-3)(8x+2)=(4x+1)(4x-1)-3
Bài 1: Rút gọn biểu thức :A=\(\left(\frac{x^2-2x}{2x^2+8}-\frac{2x^2}{8-4x+2x^2-x^3}\right).\left(1-\frac{1}{x}-\frac{2}{x^2}\right)\)
Tìm x biết
1) x3 - 9x2 + 27x = -8
2) (2x - 1)3 - 4x2 (2x - 3) = 5
3) (x + 3)2 + x(3x + 1)2 + (2x + 1)(4x2 - 2x + 1) - 3x2 = 54
4) (x + 1)3 - (x - 1)3 - 6(x - 1)2 = -10
5) 8x3 - 60x2 + 150x - 125 = 4
x^2-4x+8=2x-1
Tìm x
8 Tìm x biết : a) 5x(4x-5)-4x(5x-6)-30 ; 2x(6-3x)+3x(2x-5)=12
cho biểu thức
M = \(\left(\dfrac{x^2-2x}{2x^2+8}-\dfrac{2x^2}{8-4x+2x^2-x^3}\right).\left(1-\dfrac{1}{x}-\dfrac{2}{x^2}\right)\)
a) Rút gọn biểu thức M
b) Tính giá trị của M với x = \(\dfrac{1}{2}\)
Rút gọn:
c.)(7x-8)(7x+8)-10(2x+3)2+5x(3x-2)2-4x(x-5)2.
d.) (x2-3)(x2+3)-5x2(x+1)2-(x2-3x)(x2-2x+4x)(x+2)2
BÀI 8: THU GỌN VÀ TÌM BẬC CỦA MỖI ĐA THỨC:
A= -2xy + 3/2xy^2 + 1/2xy^2 + xy
B= xy^2z + 2xy^2z - xyz - 3xy^2z + xy^2z
C= 4x^2y^3 + x^4 - 2x^2 + 6x^4 - x^2y^3
D= 3/4xy^2 - 2xy - 1/2xy^2 + 3xy
E= 2x^2 - 3y^3 - z^4 - 4x^2 + 2y^3 + 3z^4
F= 3xy^2z + xy^2z - xyz + 2xy^2z -3xyz